Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1365-2672.1994.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Legionella from water samples using various culture methods

Abstract: The efficacy of a non-selective medium and two selective media were compared for the isolation of legionellas from water samples. The effect of acid wash treatment for decontamination of the water samples on the isolation frequency of legionellas was also studied. The 236 samples were taken from cooling, humidifying and drinking water systems; 21% were legionella-positive when inoculated directly on modified Wadowsky-Yee (MWY) medium and 26% were positive when concentrated (x 200) before cultivation on MWY or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
(27 reference statements)
1
9
1
Order By: Relevance
“…1986; Stout et al . 1992; Kusnetsov et al . 1994), direct inoculum detected significantly higher concentrations compared with the techniques involving decontamination, which brought about an average reduction of 67–68% in detectable Legionellae.…”
Section: Discussionmentioning
confidence: 99%
“…1986; Stout et al . 1992; Kusnetsov et al . 1994), direct inoculum detected significantly higher concentrations compared with the techniques involving decontamination, which brought about an average reduction of 67–68% in detectable Legionellae.…”
Section: Discussionmentioning
confidence: 99%
“…Various media, generally containing amino acid supplements and antimicrobial Q 1999 Blackwell Science Ltd, Environmental Microbiology, 1, 283±293 inhibitors, can be used to cultivate Legionella species (Atlas, 1995). Often, pre-enrichment with various inhibitors is needed to eliminate populations of other bacteria (Roberts et al, 1987;Kusnetsov et al, 1994a). Kasuga et al (1999), for example, recently reported that combined pretreatment with acid after heating and the addition of polymyxin B and oxytetracycline into the selective cultivation medium is a useful method for the detection of Legionella sp.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Epidemiological study demonstrates that legionnaire's disease is associated with environmental water system especially with the cooling tower system (Kusnetsov et al, 1994;Craun et al, 2010). Gold standard method for detection of Legionella species is based on cultivation (Den et al, 2004).…”
Section: Discussionmentioning
confidence: 99%